2007
DOI: 10.1590/s0100-736x2007001000003
|View full text |Cite
|
Sign up to set email alerts
|

Identificação e diferenciação de herpesvírus bovino tipos 1 e 5 isolados de amostras clínicas no Centro-Sul do Brasil, Argentina e Uruguai (1987-2006)

Abstract: Os herpesvírus bovino tipos 1 e 5 (BoHV-1; BoHV-5) são genética e antigenicamente muito semelhantes e por isso são indistinguíveis pela maioria dos testes diagnósticos. Como o BoHV-1 tem sido classicamente associado com doença respiratória e genital, os herpesvírus isolados dessas enfermidades têm sido provisoriamente - e às vezes definitivamente - identificados como BoHV-1. Da mesma forma, os casos de infecção neurológica por herpesvírus em bovinos têm sido atribuídos em sua totalidade ao BoHV-5. Este trabalh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
21

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 35 publications
0
21
0
21
Order By: Relevance
“…BoHV-5 and -1 are widespread among South American cattle and cause important losses to the livestock industry (Silva et al 2007b, Suarez-Heinlein et al 1993. Although BoHV-5 infection has been described in other continents, it seems to be more prevalent in South American countries like Argentina and Brazil (Silva et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…BoHV-5 and -1 are widespread among South American cattle and cause important losses to the livestock industry (Silva et al 2007b, Suarez-Heinlein et al 1993. Although BoHV-5 infection has been described in other continents, it seems to be more prevalent in South American countries like Argentina and Brazil (Silva et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Our collaborators first reported the construction of a gE-deleted recombinant BoHV-1 intended to be used as a vaccine strain (Franco et al 2002). As BoHV-1 and BoHV-5 co-circulate in Brazilian cattle (Silva et al 2007), a commercial vaccine for use in the country would require the inclusion of both viruses. To this end, we constructed a double deletion BoHV-5 gE-and tk-mutant (BoHV-5gEΔTKΔ, Brum et al 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were grown on minimal essential medium (MEM), containing ampicillin (1.6mg/L), streptomycin (0.4mg/L), amphotericin (2mg/L), supplemented with 10% fetal bovine serum (Cultilab, Brazil). The virus used for gE cloning was the BoHV-1.2 isolate SV56/90 (Weiblen et al 1992, Silva et al 2007). The viruses used in the characterization of the recombinant proteins were Brazilian BoHV-1 (SV-265 and 265gE-) and BoHV-5 (SV507/99) strains described elsewhere (Franco et al 2002, Silva et al 2007.…”
Section: Cells Virus and Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine herpesvirus 1 has been associated with respiratory tract infections (bovine infectious rinotracheitis, IBR), abortions, sporadic cases of encephalitis and reproductive tract infections (vulvovaginitis or balanopostitis) (Engels and Ackermann 1996, Muylkens et al 2007, Nandi et al 2009. Bovine herpesvirus 5 seems to be widely distributed in Latin America (Esteves et al 2008, Pidone et al 1999, Silva et al 2007, although it has been occasionally found in other regions of the world (Bartha et al 1969, Carrillo et al 1983, Diallo et al 2010, d'Offay et al 1993, Eugster et al 1975, Kirkland et al 2009. Bovine herpesvirus 5 has been associated with encephalitis and meningoencephalitis in calves and is of utmost importance in the differential diagnosis of bovine spongiform encephalitis .…”
Section: Introductionmentioning
confidence: 99%